Comparison of inoculum sources for long-term process performance and fate of ANAMMOX bacteria niche in poly(vinyl alcohol)/sodium alginate gel beads. (October 2017) - Cho, Kyungjin; Choi, Minkyu; Jeong, Dawoon; Lee, Seockheon; Bae, Hyokwan
Abstract: The process performance and microbial niche of anaerobic ammonia oxidation (ANAMMOX) bacteria were compared in two identical bioreactors inoculated with different inoculum sources (i.e., pre-cultured ANAMMOX bacteria: PAB and activated sludge: AS) entrapped in poly(vinyl alcohol)/sodium alginate (PVA/SA) gel beads for a long-term period (i.e., 1.5 years). The start-up period with AS was longer than that with PAB; however, both bioreactors were successfully operated over the long-term with stable ANAMMOX activity. After long-term operation, the 16S rRNA gene concentration of ANAMMOX bacteria in both bioreactors was significantly increased, and thereby became comparable. In addition, Candidatus Jettenia sp. became the dominant ANAMMOX species in both bioreactors. Our results suggested that the ANAMMOX performance and microbial niche of ANAMMOX bacteria became nearly identical during long-term operation despite the use of different inoculum sources. Therefore, the use of PVA/SA gel beads entrapping AS appears to be a relevant option for constructing an ANAMMOX process in places where a full-scale ANAMMOX process has never been done previously. Graphical abstract: Highlights: Two ANAMMOX processes inoculated with different seed sources were compared. The ANAMMOX processes were successfully operated long-term. The ANAMMOX process inoculated with AS was successfully started up within 93 days. The ANAMMOX 16S rRNA gene copies of the reactors became comparable after 1.5 years. Candidatus Jettenia sp. was dominant in both PVA/SA gel beads ANAMMOX processes.